2004
DOI: 10.1021/es034631f
|View full text |Cite
|
Sign up to set email alerts
|

Tire-Wear Particles as a Source of Zinc to the Environment

Abstract: Tire-tread material has a zinc (Zn) content of about 1 wt %. The quantity of tread material lost to road surfaces by abrasion has not been well characterized. Two approaches were used to assess the magnitude of this nonpoint source of Zn in the U.S. for the period 1936-1999. In the first approach, tread-wear rates from the automotive engineering literature were used in conjunction with vehicle distance-driven data from the U.S. Department of Transportation to determine Zn releases. A second approach calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
223
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 507 publications
(235 citation statements)
references
References 54 publications
8
223
2
2
Order By: Relevance
“…Lin et al, 2005;Ntziachristos et al, 2007), and non-tailpipe emissions caused by abrasion of brakes (e.g. Councell et al, 2004;Lough et al, 2005;Schauer et al, 2006;Johansson et al, 2009;Pérez et al, 2010;Apeagyei et al, 2011;Song and Gao, 2011;Harrison et al, 2012). Dall'Osto et al (2013), for example, found a comparable brake dust factor characterized by Cu and Fe with a strong 30 diurnal pattern.…”
Section: Primary Vehicle Emissionsmentioning
confidence: 99%
“…Lin et al, 2005;Ntziachristos et al, 2007), and non-tailpipe emissions caused by abrasion of brakes (e.g. Councell et al, 2004;Lough et al, 2005;Schauer et al, 2006;Johansson et al, 2009;Pérez et al, 2010;Apeagyei et al, 2011;Song and Gao, 2011;Harrison et al, 2012). Dall'Osto et al (2013), for example, found a comparable brake dust factor characterized by Cu and Fe with a strong 30 diurnal pattern.…”
Section: Primary Vehicle Emissionsmentioning
confidence: 99%
“…4,5 ZnO is the dominant species emitted from tire-treads 6 and has been identified 59 in emissions from metal smelting along with ZnS. 7 Copper has likewise been linked to 60 multiple sources, including smelting, oil combustion, wood smoke and brake wear.…”
mentioning
confidence: 99%
“…Tire-wear particles have been recognized as a source of Zn introduced into the environment near vehicle transportation routes. 24 Furthermore, Weckwerth 10 pointed out that Zn was one of the top two metals in absolute abundance in diesel soot. Cu has been previously identified as an important brake-wear metal.…”
Section: Resultsmentioning
confidence: 99%